Inflation, Unemployment and Economic Growth in Nigeria - Chidi , Wosu,; Chika Bright , Ezekwu, (Research Parks Publishers, 2025)
This study investigates the links between inflation and unemployment on economic growth in Nigeria from 1980-2023 using the Ordinary Least Square approach. The study discovered the existence of a positive relationship between interest rate, unemployment rate and economic growth but a negative links exist between inflation rate and economic growth in Nigeria within the period under consideration. The study observed that inflation established its real impact of always being negative in terms of its links with economic growth in the economy of Nigeria. The study concludes that government should provide enabling environment to produce imported goods here in Nigeria to cushion the impact of imported inflation into the Nigerian economy.